2021
DOI: 10.7150/thno.54741
|View full text |Cite
|
Sign up to set email alerts
|

Kinomic profile in patient-derived glioma cells during hypoxia reveals c-MET-PI3K dependency for adaptation

Abstract: Hypoxic microenvironment is a hallmark of solid tumors, especially glioblastoma. The strong reliance of glioma-propagating cells (GPCs) on hypoxia-induced survival advantages is potentially exploitable for drug development. Methods: To identify key signaling pathways for hypoxia adaptation by patient-derived GPCs, we performed a kinase inhibitor profiling by screening 188 small molecule inhibitors against 130 different kinases in normoxia and hypoxia. Potential kinase candidates were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Ingenuity pathway analysis (IPA) (Qiagen Inc., Germany), gene set enrichment analysis and network analysis were performed as reported. 48…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ingenuity pathway analysis (IPA) (Qiagen Inc., Germany), gene set enrichment analysis and network analysis were performed as reported. 48…”
Section: Methodsmentioning
confidence: 99%
“…Ingenuity pathway analysis (IPA) (Qiagen Inc., Germany) gene set enrichment analysis and network analysis was performed as reported. 48 Table 1. Sequence of gene-specific primer pairs used for RT-PCR Thereafter, the cells were harvested via trypsinization and centrifugation (1,500 rpm for 3 min), followed by a PBS wash.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…MDA‐9 suppresses high levels of autophagy by phosphorylating BCL2 and EGFR signaling to achieve self‐protection 45,46 . Besides, regarding autophagy, PAK1‐mediated phosphorylation of ATG5 and phosphorylation of c‐MET and PI3K in GPCs under hypoxia conditions could affect cell autophagy 47,48 . There was an experiment that revealed that the phosphorylation level of p62/SQSTM1 was reduced in the presence of PIM knockdown.…”
Section: The Regulatory Role Of Phosphorylation As a Target In Glioma...mentioning
confidence: 99%
“…It has been reported that tepotinib, a potent c-Met inhibitor, exhibits promising activity in advanced HCC with c-Met overexpression in clinical studies, indicating that c-Met may serve as a therapeutic target for HCC [ 5 ]. Recent studies have demonstrated that activation of c-Met can modulate the redox protective nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) and downregulate reactive oxygen species (ROS), eventually inhibiting the death of cancer cells [ 6 ]. Treatment combined with c-Met and HO-1 inhibitors can promote ROS-induced oxidative stress and markedly reduce tumor growth [ 7 ].…”
Section: Introductionmentioning
confidence: 99%